New Evidence for Cotinus coggygria Scop. Extracts Application in Gastrointestinal Ailments - Dejan Stojković; Nina Dragičević; Marija Ivanov; Nevena Gajović; Milena Jurišević; Ivan Jovanović; Marina Tomović; Jelena Živković (Pharmaceuticals)
Background/Objectives: Cotinus coggygria Scop. is traditionally used for treatment of various gastrointestinal ailments. In this study, we investigated the phytochemical profile and biological activities of leaves, bark and flowers extracts of C. coggygria. Methods: Phytochemical analysis was performed using HPLC. The antimicrobial activity of water and methanolic extracts of C. coggygria leaves, bark and flowers towards various oral fungal and bacterial strains of clinical origin was tested by use of a microdilution assay. Additionally, their cytotoxic activity was determined against different gastrointestinal carcinoma cell lines (CAL27, FaDu, SW480, HCT116 and MRC-5) in concentrations ranging from 3.125 to 400 µg/mL for 48 and 72 h. Results: The presence of numerous flavonoid and phenolic compounds such as sulfuretin, gallic acid, rutin, hyperoside, and isoquercitrine was detected. Micrococcus luteus, Streptococcus parasanguinis, and Candida tropicalis were the most sensitive microbiological species, with MICs of 0.12 mg/mL for the most effective extracts. Additionally, the cytotoxic activity of the samples against different gastrointestinal carcinoma cell lines (CAL27, FaDu, SW480, HCT116, and MRC-5) was determined in concentrations ranging from 3.125 to 400 µg/mL. Among the tested samples, the methanolic leaf extract exhibited the highest cytotoxic capacity, and the possible mechanism could be related to its inhibitory effect on the release of proinflammatory cytokine in CD4+ cells. Conclusions: The traditional use of C. coggygria for gastrointestinal diseases may be substantiated by its ability to inhibit the growth of harmful microorganisms and its promising cytotoxic properties. The methanolic leaf and flower extracts show significant potential for future clinical applications, and further studies are warranted to explore their mechanisms and applications in medical treatments.